The Role of Customary Institutions in the Enforcement of Customary Law in the Modern Era - Rabiah. Z Harahap (Fox Justi : Jurnal Ilmu Hukum, 2026)
Customary institutions constitute an essential component of Indonesia’s plural legal system, serving as traditional mechanisms for regulating social order and enforcing customary law within indigenous communities. However, the era of modernization and globalization has posed significant challenges to the sustainability and effectiveness of these institutions, particularly due to the dominance of positive law, socio-cultural transformation, and weakening regulatory support. This study aims to analyze the role of customary institutions in enforcing customary law in the modern era, identify factors affecting their effectiveness, and formulate strategies to strengthen their existence within the national legal system. The research employs a normative juridical method with a qualitative approach, utilizing literature review and secondary legal materials as the primary sources of data. The findings reveal that customary institutions continue to play a vital role in resolving disputes, preserving local wisdom, and maintaining social harmony in customary law communities. Nevertheless, their effectiveness has diminished as a result of modernization, urbanization, declining community compliance, and limited legal recognition. The study concludes that strengthening customary institutions requires institutional reinforcement, clearer regulatory frameworks, and synergistic integration between customary law and positive law. Such measures are necessary to ensure the realization of a balanced and just legal pluralism that acknowledges indigenous values while aligning with national legal development.